Penerapan Metode Cased Based Reasoning dalam Mendiagnosa Penyakit TB Paru Berbasis Web: Studi Kasus: PKM Kabukarudi - Susila Mete; Andreas Ariyanto Rangga; Agustina Purnami Setiawi (Neptunus: Jurnal Ilmu Komputer Dan Teknologi Informasi, 2024)
Collaboration of computer science disciplines with other disciplines has been widely carried out, for example, medical science. Expert systems for disease diagnosis are one of the many computer programs used by doctors to assist them in their work and provide good results. Researchers in the field of artificial intelligence are working to improve existing systems to cover their shortcomings. Expert systems are used in many applications for disease diagnosis. Expert systems have been used in various industries and have had a significant impact. An innovative method for diagnosing diseases is the application of case-based reasoning systems, compared to expert systems. The solution to diagnosing and treating diseases can be found in the expert system for diagnosing pulmonary tuberculosis. Because this web-based system is based on a web application, all pulmonary tuberculosis patients can access it. A rule-based system that applies the CBR method can identify various types of diseases through the use of weighting techniques and offer treatment recommendations.